SHANGHAI COOPERATION ORGANIZATION AS A REGIONAL CORNERSTONE: REGIONALIST CRITIQUES (Journal of history, 2022)
The Shanghai Cooperation Organisation has had its critics since its inception in 2001 with regards to how meaningful and organisation it really is, and its capabilities in becoming a regional cornerstone. The purpose of this piece is to critically evaluate how any why the SCO has struggled to establish itself, through the main directions of Russian and Chinese power projection and what effect that has on the SCO’s region building capability. The significance of this work lies in bridging traditionally competing schools of thought on regionalism: classical regionalist and new regionalist approaches. The analytical utility of classical approaches account well for power projection, but are not sufficient to explore the role of the SCO as an institution within which a community of like-minded states interact and reify shared norms. The use of either approach in isolation therefore struggles to account for the intricacies of the SCO, and thus limits the explanatory potential of critical approaches to the SCO as an organisation. The significance thus lies in a recognition of the need for theoretical flexibility when dealing with regional organisations that do not quite fit the normative culture of recent new regionalist schools of thought, instead adopting a more multi-faceted critical approach to harness the explanatory power of multiple theories for a single-case study.